High-temperature and high-pressure online nuclear magnetic resonance testing for CO2 flooding in Daqingzijing Oilfield - Wang, YuNing; Bao, Zhidong; Li, Zhongcheng; He, Sijie; Fang, Feifei (Frontiers in Earth Science, 2025)
As global energy demand continues to grow, enhancing the recovery rate of mature oilfields has become an important research task. CO2 flooding, as an effective enhanced oil recovery (EOR) technique, has received extensive attention in recent years. However, the multiphase flow and oil mobilization mechanisms during CO2 flooding are not fully understood, particularly under the actual high-temperature and high-pressure conditions in oilfields. Optimizing CO2 flooding techniques to improve recovery rates in these conditions has become an urgent issue. In this paper, high-temperature and high-pressure online nuclear magnetic resonance (NMR) testing technology is employed to simulate the formation conditions of the Daqingzijing Oilfield. Online NMR testing experiments are conducted with varying injection rates and flooding methods. The results indicate that regardless of slug size or injection rate, the remaining oil volume in both core samples is significantly reduced. Smaller slug sizes and lower injection rates result in less remaining oil and better displacement effect. As the slug size increases from 0.1 PV to 0.4 PV, the average recovery rate decreases by approximately 7%. Similarly, when the injection rate increases from 0.01 mL/min to 0.04 mL/min, the average recovery rate decreases by around 8%. Furthermore, there are significant differences in oil displacement effect among different flooding methods. The foam system exhibits the highest oil displacement effect, followed by water-gas alternating flooding, continuous gas injection, and finally water flooding followed by continuous gas injection. Compared to water flooding followed by continuous gas injection, continuous gas injection increases the average recovery rate by about 8%, water-gas alternating flooding increases it by about 13%, and the foam system increases it by about 18%. This study not only deepens the understanding of the CO2 flooding process but also provides scientific basis and technical support for formulating more reasonable CO2 flooding schemes and improving recovery rates.